Cholangiocarcinoma PDHA1 succinylation suppresses macrophage antigen presentation via alpha-ketoglutaric acid accumulation - Ning Zhang; Linmao Sun; Shuo Zhou; Changyong Ji; Tianming Cui; Qi Chu; Jiareng Ye; Shuhang Liang; Kun Ma; Yufeng Liu; Xianying Li; Xinyu Guo; et al. (Nature Communications)
Abstract Gemcitabine combined with cisplatin is the first-line chemotherapy for advanced cholangiocarcinoma, but drug resistance remains a challenge, leading to unsatisfactory therapeutic effect. Here, we elucidate the possibility of chemotherapy regimens sensitized by inhibiting succinylation in patients with cholangiocarcinoma from the perspective of post-translational modification. Our omics analysis reveals that succinylation of PDHA1 lysine 83, a key enzyme in the tricarboxylic acid cycle, alters PDH enzyme activity, modulates metabolic flux, and leads to alpha-ketoglutaric acid accumulation in the tumor microenvironment. This process activates the OXGR1 receptor on macrophages, triggering MAPK signaling and inhibiting MHC-II antigen presentation, which promotes immune escape and tumor progression. Moreover, we show that inhibiting PDHA1 succinylation with CPI-613 enhances the efficacy of gemcitabine and cisplatin. Targeting PDHA1 succinylation may be a promising strategy to improve treatment outcomes in cholangiocarcinoma and warrants further clinical exploration.